127 Hepatic involvement as a presentation in pediatric lupus: a retrospective study of 3 cases. (April 2019) - Singh, Ankita; Anjani, Gummadi; Pilania, Rakesh; Jindal, Ankur; Vignesh, Pandiarajan; Suri, Deepti; Singh, Surjit
Abstract : Background: Though abnormal liver tests can be seen during the course of disease in lupus, liver involvement as a presenting manifestation is uncommon in children with lupus. Methods: We retrospectively studied 140 pediatric lupus patients from January 1993- November 2018 and collected clinical and laboratory data of patients (3) who had liver involvement as presenting manifestation. Results: Case 1 was 13-year-old girl with fever and joint pain for 7 months associated with rash and yellow discoloration of eyes and body for 1 month. She also had altered behavior for 3 days. Examination revealed malar rash, pallor, jaundice, bilateral knee arthritis and hepatosplenomegaly. Investigations revealed (table 1 ) anemia, thrombocytopenia and lymphopenia. She had conjugated hyperbilirubinemia. Transaminases were elevated. Further investigations confirmed diagnosis of lupus (table 1 ). Markers for autoimmune hepatitis (SMA; LKM) were negative. She received pulse methylprednisolone followed by tapering doses of oral prednisolone. In view of neurological involvement she also received cyclophosphamide and shifted to azathioprine later. Her initial SLEDAI-2k was 22, that decreased to 4 at 2 year follow-up. Case 2 was a 11-year-old boy with fever, rash and joint pain for 1 month. Examination revealed pallor, malar rash, oral ulcers, arthritis of bilateral elbow and knee and hepatomegaly. Investigations (table 1 ) revealed anemia; thrombocytopenia; leucopenia and lymphopenia. In view of multisystem involvement a possibility of lupus was considered which was confirmed by investigations (table 1 ). He had elevated transaminases. There was no coagulopathy. He was started on oral prednisolone. She also had class 3 lupus nephritis and received pulse cyclophosphamide followed by azathioprine in maintenance. Her transaminases decreased in follow-up. Her initial SLEDAI-2k was 18, that decreased to 2 at 2 year follow-up. Case 3 was an 9-year-old girl who had rash and abdominal distention for 20 days and fever and altered sensorium for 6 days. On examination she had pallor, malar rash, ascitis and hepatosplenomegaly. Investigations revealed anemia; thrombocytopenia; leucopenia and lymphopenia. She had conjugated hyperbilirubinemia, elevated transaminases and coagulopathy. She also had deranged renal function tests. Ultrasonography reveals coarse echotexture, gross ascitis and splenomegaly. Possibility of lupus with acute on chronic liver decompensation was considered which was confirmed by investigations (table 1 ). She was given methyl prednisolone. She had progressive azotemia so possibility of rapidly progressive renal failure was considered and cyclophosphamide was given. However, she developed refractory shock and eventually expired. Conclusions: Hepatic involvement at presentation in lupus can be multifaceted and poses challenge in diagnosis. Funding Source(s): None